Frequency and Topography of AstrocyticTumor: Experience of 567 Cases at Referral Neuroscience Hospital in Bangladesh (Journal of National Institute of Neurosciences Bangladesh, 2020)
Background: Glioma is the most commonly occurring malignant brain tumor that varies by age, sex, race or ethnicity. A very few number of records on CNS tumors are available in Bangladesh. National Institute of Neurosciences and Hospital (NINS), Dhaka has a good number of CNS surgeries. Regularly both tumorous and non-tumorous ICSOL samples are examined here.Objective: The aim of the study was to see the subtypes, frequency and topography of Astrocytic tumors at NINS setting.Methodology: Data from the department of Neuropathology department of NINS since January 2013 to June 2019 were evaluated. Tissue were fixed in formalin, paraffin embedded, stained with H&E. Histomorphology and WHO 2007 CNS tumor classification were used.Result: From 3945 routine sample 567 cases were sorted out as Astrocytic tumor. Total male were 61% (346) and female 39% (221), male to female ratio was 1.6:1. The mean age was 32.64 and ranged from 1 to 80 years. Sixty six percent (66%) tumors were in supratentorial compartment, 15% infratentorial, 6.3% spinal and 9.7% in midline areas like thalamus, hypothalamus and seller region. In this study 34.6% (196) cases were Glioblastoma, followed by Anaplastic Astrocytoma 8.3%(47), Diffuse Astrocytoma 29% (165), Pilocytic Astrocytoma 26.6% (151), Pilomyxoid Astrocytoma 0.4% (2), Subependymal giant cell Astrocytoma 0.9% (5) and Pleomorphic Xanthoastrocytoma 0.1 (0.1). Topographically 66% glial tumors are supratentorial. Among the glial tumors 34.6% is Glioblastoma, 8.3% Anaplastic Astrocytoma, 29% Diffuse Astrocytoma and 26.6% Pilocytic astrocytoma. Common age group of Glioblastoma is 41-60 (52%) years, diffuse astrocytoma is 21-40 years 60.60 and Pilocytic Astrocytoma is 1-20 years (66.88). Glioblastoma, Anaplastic Astrocytoma and Diffuse astrocytoma are more common in male than female.Conclusion: There is no gender difference in case of Pilocytic Astrocytoma.Journal of National Institute of Neurosciences Bangladesh, 2020;6(2): 91-95